Biotechnology approaches for production of antiulcerogenic dihydro-epideoxyarteannuin B isolated from Artemisia annua L. - Marques, Daniela A.; Foglio, Mary A.; Morgante, Patrícia G. [UNESP]; Van Sluys, Marie-anne; Shepherd, Simone L. Kirszenzaft (Sociedade Brasileira de Farmacognosia, 2006)
Methodologies were developed for the establishment and cultivation of Artemisia annua L (CPQBA 2/39 x PL5 hybrid) roots submitted to light conditions and genetic transformation performed with Agrobacterium rhizogenes (15834 and 8196 strains). The transgenic and non-transgenic (normal) roots were cultured in Murashige and Skoog (1962) medium, kept under different photoperiodic conditions and analyzed for evaluation of the antiulcerogenic dihydro-epideoxyarteannuin B (compound A) contents. The Dot Blot technique was used to confirm the transgenic nature of the roots. The plants¢s crude extracts were analyzed by Gas Chromatography coupled to Mass Spectrum (CG/MS). The chromatograms of the extracts taken from normal roots revealed the presence of dihydro-epideoxyarteannuin B and other compound (compound B). Photoperiods during cultivation influenced the production of these two compounds: under continuous darkness dihydro-epideoxyarteannuin B was intensely produced and the compound B present in small amounts, while on 16 h photoperiod, the inverse occurred. The quantification of dihydro-epideoxyarteannuin B by Gas Chromatography coupled to Flame Detector Ionization (CG/FID) revealed an approximately fivefold increase in the production of this compound by normal roots kept under continuous darkness compared to roots kept under 16 h light period. The terpene dihydro-epideoxiarteannuin B was not present in transgenic hairy roots.

Foram desenvolvidas metodologias para o estabelecimento e cultivo de raízes de Artemisia annua L. (híbrido CPQBA 2/39 x PL5). Estas raízes foram submetidas a diferentes condições de luz e a transformação genética com Agrobacterium rhizogenes (cepas 8196 e 15834). As raízes transgênicas e não-transgênicas (normais) foram cultivadas em meios de Murashige e Skoog (1962), mantidas sobre diferentes condições de fotoperíodo e analisadas para avaliação do conteúdo do composto antiulcerogênico dehidro-epideoxiarteanuína B (composto A). A confirmação do caráter transgênico das raízes foi obtida por Dot Blot. Os extratos dos materiais vegetais foram analisados por Cromatografia Gasosa acoplada a um Espectômetro de Massas (CG/EM). Os cromatogramas dos extratos das raízes normais revelaram a presença de dehidro-epideoxiarteanuína B e de um outro composto (composto B). As condições fotoperiódicas de cultivo influenciaram na produção destes dois compostos, sendo que sobre condição de escuro contínuo, dehidro-epideoxiarteanuína B foi intensamente produzido e o composto B foi detectado em pequenas proporções, enquanto que sob fotoperíodo de 16 horas, o inverso ocorreu. A quantificação de dehidro-epideoxiarteanuína B por Cromatografia Gasosa acoplada a um Detector de Ionização de Chamas (CG/FID) revelou um aumento de aproximadamente cinco vezes na produção deste composto pelas raízes normais cultivadas sobre escuro contínuo em relação às raízes cultivadas na presença de 16 horas de luz. O terpeno dehidro-epideoxiarteanuína B não estava presente nas raízes transgênicas.
Ferramentas biotecnológicas para a produção de dihidro-epideoxiarteanuina B, um antiulcerogênico isolado de Artemisia annua L.
Keywords: Artemisia annua; terpene; in vitro roots culture; hairy roots; light; Artemisia annua; terpeno; cultura de raízes in vitro; raízes transgênicas; luz